The Effect of Antiretroviral Therapy for the Treatment of Human Immunodeficiency Virus (HIV)-1 in Pregnancy on Gestational Weight Gain . (3rd December 2021) - Joseph, Naima T; Satten, Glen A; Williams, Rachel E; Haddad, Lisa B; Jamieson, Denise J; Sheth, Anandi N; Badell, Martina L
Abstract: Background: Gestational weight gain above Institute of Medicine recommendations is associated with increased risk of pregnancy complications. The goal was to analyze the association between newer HIV antiretroviral regimens (ART) on gestational weight gain. Methods: A retrospective cohort study of pregnant women with HIV-1 on ART. The primary outcome was incidence of excess gestational weight gain. Treatment effects were estimated by ART regimen type using log-linear models for relative risk (RR), adjusting for prepregnancy BMI and presence of detectable viral load at baseline. Results: Three hundred three pregnant women were included in the analysis. Baseline characteristics, including prepregnancy BMI, viral load at prenatal care entry, and gestational age at delivery were similar by ART, including 53% of the entire cohort had initiated ART before pregnancy ( P =  nonsignificant). Excess gestational weight gain occurred in 29% of the cohort. Compared with non–integrase strand transfer inhibitor (-INSTI) or tenofovir alafenamide fumarate (TAF)–exposed persons, receipt of INSTI+TAF showed a 1.7-fold increased RR of excess gestational weight gain (95% CI: 1.18–2.68; P  < .01), while women who received tenofovir disoproxil fumarate had a 0.64-fold decreased RR (95% CI: .41–.99; P  = .047) of excess gestational weight gain. INSTI alone was not significantly associated with excess weight gain in this population. The effect of TAF without INSTI could not be inferred from our data. There was no difference in neonatal, obstetric, or maternal outcomes between the groups. Conclusions: Pregnant women receiving ART with a combined regimen of INSTI and TAF have increased risk of excess gestational weight gain. Abstract : Pregnant women receiving ART with both integrase strand transfer inhibitor (INSTI) and tenofovir alafenamide fumarate (TAF) have increased risk of excess gestational weight gain, while tenofovir disoproxil fumarate use may be protective, irrespective of INSTI use.